Highly sensitive colorimetric detection of HgII and CuII in aqueous solutions: from amino acids toward solid platforms. Issue 3 (4th December 2014) - Park, Jooyoung; In, Byunggyu; Neupane, Lok Nath; Lee, Keun-Hyeung
Abstract : A chemosensor (NBD-H ) based on an amino acid with 7-nitro-2, 1, 3-benzoxadiazole was used for selective detection of Hg II and Cu II among 15 metal ions in aqueous solutions by a colorimetric change and fluorescence change. Abstract : A chemosensor (NBD-H ) based on an amino acid with 7-nitro-2, 1, 3-benzoxadiazole was used for selective detection of Hg II and Cu II among 15 metal ions in aqueous solutions by a colorimetric change.NBD-H sensitively differentiated Hg II and Cu II in aqueous solutions by a color change; a pink color for Hg II and an orange color for Cu II .NBD-H showed nanomolar detection limits for Hg II (176 nM, R 2 = 0.996) and Cu II (163 nM, R 2 = 0.996). The detection limit for Cu II was much lower than the maximum allowable level of Cu II in drinking water recommended by the U.S. EPA. The binding mode study showed that deprotonation of the NH group ofNBD-H played a critical role in the binding and sensing of metal ions.NBD-H immobilized on PEG-PS resin maintained the potent binding affinity and sensing ability for the metal ions. The resin withNBD-H was recyclable for the detection of metal ions in 100% aqueous solutions.